2014
DOI: 10.1186/1472-6939-15-59
|View full text |Cite
|
Sign up to set email alerts
|

The over-optimistic portrayal of life-supporting treatments in newspapers and on the Internet: a cross-sectional study using extra-corporeal membrane oxygenation as an example

Abstract: BackgroundExtra-corporeal membrane oxygenation has been introduced to clinical practice for several decades. It is unclear how internet and newspapers portray the use of extra-corporeal membrane oxygenation. This study were: (1) to quantify the coverage of extra-corporeal membrane oxygenation use in newspapers and on the Internet; (2) to describe the characteristics of extra-corporeal membrane oxygenation users presented in newspaper articles and the Internet web pages in comparison with those shown in extra-c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 19 publications
0
12
0
Order By: Relevance
“…Chen et al [23] also reported that information reported in the major newspapers in Taiwan regarding the use of life supporting treatments for patients who are critically ill is too optimistic as indicated by the probability of survival. In addition to health-related information regarding life supporting treatments in the media, Moynihan et al [24] studied media coverage of the benefits and risks for three medications in leading national newspapers, local newspapers, and television networks in the United States.…”
Section: Discussionmentioning
confidence: 99%
“…Chen et al [23] also reported that information reported in the major newspapers in Taiwan regarding the use of life supporting treatments for patients who are critically ill is too optimistic as indicated by the probability of survival. In addition to health-related information regarding life supporting treatments in the media, Moynihan et al [24] studied media coverage of the benefits and risks for three medications in leading national newspapers, local newspapers, and television networks in the United States.…”
Section: Discussionmentioning
confidence: 99%
“…We also expect that being connected and informed, patients will be better empowered to take control of their health and demand better value [ 3 ], eventually leading to improved quality and reduced costs of health care, although some of these expectations have yet to be proven [ 4 ]. However, despite the promises of eHealth, some of the online information may be inaccurate or even harmful [ 5 , 6 ]. With the digital transformation of patient education media, patients are becoming increasingly responsible for evaluating the accuracy and reliability of the information they find over the Internet, which assumes non-trivial skills: electronic health literacy (eHealth literacy).…”
Section: Introductionmentioning
confidence: 99%
“…Prior studies have proposed the possibility that the significantly increased ECMO uses in Taiwan’s population might be associated with significant social events [ 6 ] and their related over-optimistic reports on the Internet and newspapers [ 34 ]. We also highlighted the possibility that the media literacy of the audience, i.e.…”
Section: Discussionmentioning
confidence: 99%